تقييم الإنتاج المشترك للطاقة في محطة توليد إكسيرجيا - عدنان عمران; موسى المحمد (Tishreen University, 2019)
تتصف أنظمة محطات توليد الطاقة الكهربائية التي تستخدم التوربينات البخارية بمردود حراري وإكسيرجي منخفض نسبيا وبجودة إكسيرجية منخفضة نظرا لجملة تحولات الطاقة من شكل إلى آخر لنحصل في النهاية على طاقة كهربائية. يعرض البحث التالي إمكانية رفع مردود هذه المحطات وتحديد أماكن الضياعات فيها باستخدام الطريقة الإكسيرجية. يتناول البحث حساب الضياعات الإكسيرجية والمردود الإكسيرجي لمحطتي توليد طاقة، إحداهما تكثيفية ذات مخرج واحد والأخرى كهر وحرارية ذات مخرجين وتشتركان بإنتاج استطاعة كهربائية واحدة.   The electrical energy generation plant systems, in which the steam turbine is used, represent a law exergy and heat efficiency as well as a law exergy qulaity due to the energy change from one form into another. The following research represents the possibility of increasing plant output and limiting loss using the exergy method. The research calculates both the exergy losses and the exergy efficiency for two-energy generation plants, one with mono-output and the other with two-outputs. They both produce mono-electrical power.